2018
DOI: 10.1021/acs.iecr.8b01527
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Analysis of Double Logistic Distributed Activation Energy Model for Thermal Decomposition Kinetics of Solid Fuels

Abstract: The distributed activation energy model (DAEM) has been widely used to analyze the thermal decomposition of solid fuels such as lignocellulosic biomass and its components, coal, microalgae, oil shale, waste plastics, and polymer etc. The DAEM with a single distribution of activation energies cannot describe those reactions well since the thermal decomposition normally involves multiple sub-processes of various components. The double DAEM employs a double distribution to represent the activation energies. The G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 62 publications
0
13
0
Order By: Relevance
“…Through the FTIR analysis of DPWP, we observed that all DPWP showed similar functional groups with varying spectral intensities across the measured spectrum (Figure 3). The absorption bands around 1260-1034 cm −1 were assigned to C-O-C and C-O bond stretching in the aryl ether groups present in cellulose and lignin [40,41]. The spectral bands at 1649, 1527, and 1649 cm −1 were attributed to the C=C vibration of the aromatic ring, C-H bending, and C=C aromatic skeletal vibrations, respectively [41,42].…”
Section: Ftir Analysis Of Dpwpmentioning
confidence: 99%
See 2 more Smart Citations
“…Through the FTIR analysis of DPWP, we observed that all DPWP showed similar functional groups with varying spectral intensities across the measured spectrum (Figure 3). The absorption bands around 1260-1034 cm −1 were assigned to C-O-C and C-O bond stretching in the aryl ether groups present in cellulose and lignin [40,41]. The spectral bands at 1649, 1527, and 1649 cm −1 were attributed to the C=C vibration of the aromatic ring, C-H bending, and C=C aromatic skeletal vibrations, respectively [41,42].…”
Section: Ftir Analysis Of Dpwpmentioning
confidence: 99%
“…The absorption bands around 1260-1034 cm −1 were assigned to C-O-C and C-O bond stretching in the aryl ether groups present in cellulose and lignin [40,41]. The spectral bands at 1649, 1527, and 1649 cm −1 were attributed to the C=C vibration of the aromatic ring, C-H bending, and C=C aromatic skeletal vibrations, respectively [41,42]. Furthermore, the bands in the range between 2371 and 2098 cm −1 were characteristic of C=O stretching present in the carboxylic, ketone, and aldehyde groups [42].…”
Section: Ftir Analysis Of Dpwpmentioning
confidence: 99%
See 1 more Smart Citation
“…The biochar gasification is the committed step, which is due to its low conversion rate and higher activation energy compared to the raw material pyrolysis stage [21]. The reaction kinetics are critical in process development, as they provide important parameters for reactor design and process modelling [22]. Some research showed that the kinetic parameters of different biochar produced by different conditions are not the same [3,18,23].…”
Section: Introductionmentioning
confidence: 99%
“…In view of these urgent issues in energy and environment, many countries including China (the world's largest greenhouse gas emitter) are taking substantial measures to promote a greater use of renewable energy resources to reduce the heavy dependence on fossil fuels [3]. Among existent renewable energy sources, biomass has attracted immense attention because it is a promising and cost-effective feedstock to produce clean and renewable biofuels [4,5]. Biomass can be exploited to produce biofuel, heat or chemicals via different conversion technologies.…”
Section: Introductionmentioning
confidence: 99%